2015
DOI: 10.4103/2229-5178.169713
|View full text |Cite
|
Sign up to set email alerts
|

Gianotti-Crosti Syndrome following immunization in an 18 months old child

Abstract: Gianotti–Crosti syndrome (GCS) is an uncommon dermatological condition characterized by distinct, self-limiting, symmetrical, erythematous, papulovesicular eruptions distributed mainly on the extremities, buttocks and face in young children. Although GCS is commonly attributed to viral infections, vaccinations too can rarely precipitate this condition. We report a rare case of GCS following diptheria, pertussis, and tetanus (DPT) and oral polio immunisation in an 18-month-old child along with a review of simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Males outnumbered females with a ratio of 1.57:1.0. Gianotti-Crosti syndrome commonly affects children between two to six years of age [30]. In the present study too, the majority of the cases belonged to the age group of 2-5 years (29.4%).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Males outnumbered females with a ratio of 1.57:1.0. Gianotti-Crosti syndrome commonly affects children between two to six years of age [30]. In the present study too, the majority of the cases belonged to the age group of 2-5 years (29.4%).…”
Section: Discussionsupporting
confidence: 58%
“…Babu and Arivazhahan [30] No cases of parapsoriasis and pityriasis rubra pilaris were reported in the present study. The low number of patients may be accountable for this.…”
Section: Authors Agementioning
confidence: 42%
See 2 more Smart Citations
“…It was also reported that an 18‐month‐old child developed classical GCS rash 3 days after diphtheria, pertussis, tetanus, and oral polio vaccinations . However, the role of oral polio per se in this patient would be unknown, as four vaccines were administered concomitantly.…”
Section: Introductionmentioning
confidence: 89%